Knowledge on acute kidney injury among nurses working in a tertiary hospital - Sapkota, Abja; Sedhain, Arun; Karki, Usha (Journal of Chitwan Medical College, 2020)
Background: Nurses can play a pivotal role to identify and prevent acute kidney injury (AKI) at the earliest and their level of understanding about the disease remains quite important. So, this study was conducted with an aim of assessing the level of understanding of AKI among nurses. Methods: A cross-sectional descriptive study was conducted among 122 nursing staffs working at different wards of a tertiary hospital. Knowledge on AKI was evaluated on different headings-definition, risk factors, bed side nursing observations, and supportive care. Semi-structured questionnaire was used to collect the responses through self-administered method. Analysis was done through frequency, percentage median, chi-square test and through odds ratio using Microsoft Excel and SPSS version 16 for windows. Results: A total of 122 nurses were included in the study. Mean age of the respondents was 26.7±5.88 years. Only 43.4% of the respondents could correctly define AKI on the basis of creatinine value. Non-steroidal anti-inflammatory drugs (NSAIDs) and aminoglycosides as nephrotoxic drugs could be listed by 59.8% and 23.7% of the respondents respectively. About 40% of the nurses mentioned the requirement of observation of both intake and output as a part of management of AKI. Overall, 53.3% of the nurses were found to have an inadequate knowledge of AKI. Conclusions: Inadequate knowledge of AKI among nurses can hinder the early recognition and management. Therefore, there seems to be a strong need of formal and structured refreshing course for the nurses to provide current updates on identification, risk assessment, recognition and response of AKI.